Post traumatic growth and related factors among adult Syrian refugees living in Turkey - Safi, Sena Akbay (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: As Syrian crisis has reached its 10th year, this paper explores the post traumatic growth and the related factors among Syrian refugees living in Turkey, with the aim of having a better understanding of the predictors of PTG and the risk factors that may play a role in the inhibition of the growth. In this cross-sectional study, we calculated that the needed sample size was 275 people, taking the sampling error to be 5.0%, with a two-sided test, 95% confidence level, power of 80%. The response rate was 78.9 %. Approval for this study was provided by the İstanbul Bilgi University Research Ethics Board. Post Traumatic Growth Inventory (PTGI), Harvard Trauma Questionnaire (HTQ), Brief COPE, General Self-Efficacy Scale (GSES), PTSD Checklist for DSM-5 (PCL-5), and sociodemographic information form were used for data collection by a self-reported online survey. Bivariate associations were estimated using chi-square tests, t-test, correlation or analyses of variance depending on variable types. Risk factors and predicting factors associated with any of the outcomes of interest and covariates associated with both risk factors and outcomes at P < 0.05 were retained in multiple regression models to examine the relationships between the independent and the control of the confounding factors. The fit of model was tested using the Durbin-Watson goodness-of-fit test. Of the 217 displaced Syrian refugees completed the questionnaires, the mean age was 32.6 ± 9.4 years ranged from 18 to 88. Growth was found to be highest in the personal strengths and new possibilities domain of growth and the results indicated that protective factors that predicted the growth significantly were the consistency between the person’s work with their education, economic status of the participant, education level, number of children, self-efficacy, level of the Turkish, active coping style, religious coping and self-distraction (P<0.05). Risk factors were number of traumatic events, and the PTSD symptoms the person has been displaying and self-blame as a coping (P<0.05). Whereas no significant relationship was found for the variables of marital status, taking support, self-distraction, emotional and instrumental support, positive reframing, planning, cultural perception, working type and age (P>0.05). In conclusion, the findings have provided a valuable insight for the domains of the growth among Syrian refugees and discussed both clinical and research based future recommendations that could be done to improve the mental health of the refugees based on the obtained results.

ÖZET: Bu çalışmanın amacı, Suriye krizinin 10. yılına ulaştığı bu dönemde, yetişkin Suriyeli mültecilerde travma sonrası büyümeyi anlamak ve ilişkili faktörleri belirlemek amacıyla yapılmıştır. Kesitsel tipteki bu araştırmada, çift yönlü test ile, %95 güven aralığı, 80% güç ve %0.05 hata payı esas alınarak 275 kişiye erişilmesi planlanmıştır. Yanıt verme hızı 78.9%’dur. Bu çalışmanın etik onayı İstanbul Bilgi Üniversitesi Araştırma Etik Kurulu tarafından verilmiştir. Online özbildirim ile, Travma Sonrası Büyüme Enventeri (PTGI), Harvard Travma Enventeri (HTQ), Kısa COPE, Genel Öz-Yeterlik Ölçeği (GSES), Post-travmatik stres bozukluğu kontrol listesi (PCL-5) ve sosyodemografik bilgi formu kullanılmıştır. Bağımlı ve bağımsız değişkenler arasındaki ilişkiyi daha iyi anlayabilmek ve karıştırıcı faktörleri kontrol edebilmek için, ikili analizlerde P<0.05 seviyesinde ilişkili bulunan değişkenler çoklu regresyon analizine dahil edilmiştir. Modelin uygunluğu, Durbin-Watson uyum iyiliği ölçütü kullanılarak test edilmiştir. Toplam 217 Suriyeli mültecinin yaşları 18 ile 88 arasında değişmiş olup, yaş ortalaması 32.6 ± 9.4’dür. Büyüme en yoğun olarak bireysel güç ve yeni fırsatlar alanında saptanmıştır. Araştırmanın sonucuna göre büyümeyi P<0.05 düzeyinde anlamlı olarak açıklayan koruyucu faktörlerin; kişinin eğitim düzeyiyle yaptığı işin uyumlu olması, ekonomik durumu, eğitim düzeyi, çocuk sayısı, öz yeterliliği, Türkçe bilme düzeyi ve aktif, dini başa çıkma biçimi olduğu, TSSB semptomları ve kendini suçlama davranışının ise risk faktörleri olduğu belirlendi (P <0.05). Medeni durum, sosyal destek alma, kültürel algı, çalışma türü, yaş ve başa çıkma stili olarak dikkat dağıtma, duygusal ve araçsal destek, olumlu yeniden çerçeveleme ve planlama değişkenleri arasında anlamlı bir ilişki bulunmamıştır (P> 0.05). Sonuç olarak, bulgular Suriyeli mültecilerdeki büyüme alanlarına ilişkin değerli bilgiler sunmuş ve elde edilen sonuçlara göre mültecilerin ruh sağlığını iyileştirmek için hem klinik hem de topluma dayalı çalışmalarda yol gösterici olabilecek değişkenleri tartışmıştır.
Türkiye'deki yetişkin Suriyeli mültecilerde travma sonrası büyüme ve ilişkili faktörler
Keywords: Traumatic Experiences; Psychological Trauma; Post-traumatic Growth; Refugee Mental Health; Conflict; Travmatik Deneyimler; Psikolojik Travma; Travma Sonrası Büyüme; Mülteci Ruh Sağlığı; Çatışma